Virtual framework customizing wearable mechanisms: An application to gait-assistive mobile hip robots - Ryu, Jegyeong; Lee, Jongjun; Yu, Jeonghan; Kang, Seok Won; Kim, Yoon Young (Elsevier BV, 2025)
Wearable robots are now beginning to transition into consumer products for everyday use, moving beyond their traditional industrial applications. For such applications, personalization is crucial to maximize the effectiveness of the robots while avoiding discomfort. We propose a virtual computational design framework specifically developed to personalize linkage mechanisms in wearable robots. This framework focuses on the design of force-transmission capabilities for gait-assistive hip wearable robot mechanisms. Incorporating an individual’s musculoskeletal modeling and gait motion, it optimizes the mechanism shape, which governs the relationship between the wearer’s hip angle and the assistive moment direction. Also, the framework simultaneously updates the actuator torque profile to maximally reduce the metabolic cost evaluated through musculoskeletal analysis. The proposed framework's effectiveness is demonstrated by customizing a single-actuator hip wearable robot; for several individuals considered, the metabolic costs for the customized robots were reduced compared to those for robots before customization or partially customized ones where only the control profiles were considered. We expect the proposed customization framework to improve the usability of consumer wearable robots by offering an affordable and lightweight personalized robot through a user-friendly virtual platform with minimal effort required from the consumer.